Opera – Oratorio Oedipus Rex by Stravinsky and the Greek Original (SPhP XI, 1996) - Skwara, Ewa (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2017)
This article is a voice in the discussion on the methods of stage implementation of Greek tragedy. The discussed staging of “Oedipus Rex” opera by Stravinsky (Tokyo ‚94) is dominated by non-verbal means of expression (music, set design, costume, stage movement), thus setting a supporting role for the libretto. Nevertheless, the performance arouses similar feelings and emotions as Sophocles’ drama.